VTI Anisotropy in the Jamieson and Echuca Shoals Formations in the Browse Basin. Issue 1 (1st December 2018) - Beji, Aymen; Pervukhina, Marina; Peyaud, Jean-Baptiste; Kovalyshen, Yevhen; Shulakova, Valeriya; Raven, Mark; Esteban, Lionel
Abstract : Overburden shales that overlie and seal hydrocarbon reservoirs usually exhibit polar anisotropy, also called Vertical Transverse Isotropy (VTI). This anisotropy is important for correct seismic inversion, seismic-to-well ties as well as having geomechanical implications. P-wave anisotropy cannot usually be determined from a vertical well unless a walkaway vertical seismic profile (VSP) has been obtained, however, such measurements are still rare. S-wave anisotropy though can be estimated from logs if the speed of sound in mud and the Stoneley wave velocity in the shale are known. Then, the P-wave anisotropy can be computed using theoretical models or empirical trends. The Stoneley wave velocity is nowadays routinely measured by sonic tools and, if a reliable mud velocity is known, the horizontal shear wave velocity (parallel to and polarised in the bedding plane) can be estimated. Thomsen's gamma parameter for S-wave anisotropy can then be calculated. If mud velocity is not known, the horizontal shear wave velocity can be obtained using calibration in an isotropic interval. Using this method, we analyse the VTI anisotropy in the Torosa-6 well in the Caswell Sub-basin of the Browse Basin, Australia. Torosa-6 drilled through the Jamieson and Echuca Shoals shaly formations where Vclay reaches 75%. Elastic anisotropy of the shaly Jamieson and Echuca Shoals Formations has been analysed. Thomsen's gamma shows a good correlation with the clay fraction in each of these formations. However for the same clay fraction, anisotropy is about 20% higher in the Jamieson Formation compared to the Echuca Shoals. This Jamieson Formation contains up to 15% of smectite, and we are investigating how this may lead to higher levels of VTI anisotropy compared with illitic clays predominant in the Echuca Shoals Formation.